2020
DOI: 10.22146/ijc.49941
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Ionic Imprinted Membrane (IIM) Synthesis Based on Acetic Polyeugenoxy Acetyl Tiophen Methanolate for Gold(III) Metal Ion Transports

Abstract: In this research, Polyeugenoxy Acetyl Tiophen Methanolate (PEATM)-Au ionic imprinted membrane (IIM) was synthesized. IIM is a PEATM based membrane that has Au(III) ion molds. The PEATM synthesis was analyzed using FTIR spectroscopy, and its relative molecular weight was determined by the viscometry method. To find out the presence of Au(III) templates on IIM, FTIR spectroscopy and SEM-EDX were used. The results of FTIR spectroscopy & SEM-EDX analysis prove the existence of Au(III) metal ion templates at II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…According to these results, in addition to the results of elemental analysis, we can suggest a tetrahedral geometry around Cd(II) ion as illustrated in Fig. 4(c) [30].…”
Section: Electronic Spectra and Magnetic Propertiessupporting
confidence: 68%
“…According to these results, in addition to the results of elemental analysis, we can suggest a tetrahedral geometry around Cd(II) ion as illustrated in Fig. 4(c) [30].…”
Section: Electronic Spectra and Magnetic Propertiessupporting
confidence: 68%
“…The literature study demonstrated that 1,2,4-triazole derivatives exhibited a wide variety of bioactivities, including antimicrobial, anticancer, anti-inflammatory, analgesic, antiviral, antidepressant, insecticide and plant growth regulator bacteria [6][7][8][9] The presence of active sites in triazole derivatives has intensively enhanced the researchers to synthesize metal complexes with such types of ligands [11][12][13]. Kanagarajan et al [13][14] have studied two biologically active Schiff base ligands derived from 1,2,4-triazole in equimolar reaction of 4-amino-5-(pyridin-4-yl)4H-1,2,4triazole-3-thiol with thiophene-2-carbaldehyde and furan-2-carbaldehyde.…”
Section: ■ Introductionmentioning
confidence: 99%